Dictionary of Finance and Investment Terms (Book). - Hendrickson, Harvey S.; H. S. H. (The Accounting Review, 1986)
Abstract Reviews the book "Dictionary of Finance and Investment Terms," by John Downes and Jordan E. Goodman.